Numerical simulation of galvanized rebars pullout (Fracture and Structural Integrity, 2014)
The usage of rebars in construction is the most common method for reinforcing plain concrete and thus bridging the tensile stresses along the concrete crack surfaces. Usually design codes for modelling the bond behaviour of rebars and concrete suggest a local bond stress – slip relationship that comprises distinct reinforcement mechanisms, such as adhesion, friction and mechanical anchorage. In this work, numerical simulations of pullout tests were performed using the finite element method framework. The interaction between rebar and concrete was modelled using cohesive elements. Distinct local bond laws were used and compared with ones proposed by the Model Code 2010. Finally an attempt was made to model the geometry of the rebar ribs in conjunction with a material damaged plasticity model for concrete.
Keywords: Pullout Test